2014
DOI: 10.1007/978-3-319-06605-9_45
|View full text |Cite
|
Sign up to set email alerts
|

Semi-supervised Clustering on Heterogeneous Information Networks

Abstract: Abstract. Semi-supervised clustering on information networks combines both the labeled and unlabeled data sets with an aim to improve the clustering performance. However, the existing semi-supervised clustering methods are all designed for homogeneous networks and do not deal with heterogeneous ones. In this work, we propose a semi-supervised clustering approach to analyze heterogeneous information networks, which include multi-typed objects and links and may contain more useful semantic information. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The key information of interest is often obscured behind redundancy and noise, and grouping the data into clusters with similar features is one way of efficiently summarizing the data for further analysis [ 1 ]. Cluster analysis has been used in many fields [ 1 , 2 ], such as information retrieval [ 3 ], social media analysis [ 4 ], neuroscience [ 5 ], image processing [ 6 ], text analysis [ 7 ] and bioinformatics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The key information of interest is often obscured behind redundancy and noise, and grouping the data into clusters with similar features is one way of efficiently summarizing the data for further analysis [ 1 ]. Cluster analysis has been used in many fields [ 1 , 2 ], such as information retrieval [ 3 ], social media analysis [ 4 ], neuroscience [ 5 ], image processing [ 6 ], text analysis [ 7 ] and bioinformatics [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [15] present a semi-supervised clustering algorithm to generate different clustering results with path selection according to user guidance. Luo et al [79] firstly introduce the concept of relation-path to measure the similarity between same-typed objects and use the labeled information to weight relation-paths, and then propose SemiRPClus for semi-supervised learning in HIN.…”
Section: B Clusteringmentioning
confidence: 99%
“…The sub dataset contains the papers published in 261 computer journals and 313 computer conferences. The schema [19] of DBLP is shown in Fig.3(a), in which Term is extracted from the titles of the papers. For the DBLP data, our recommendation problem becomes to recommend conferences to authors.…”
Section: A Datasetsmentioning
confidence: 99%
“…The works proposed by them [7][8][9][10][11][12]18] also demonstrated that by mining heterogeneous information network, one can obtain more meaningful results. It also attracted other researchers to investigate on mining the heterogeneous information network [19,23].…”
Section: B Mining Heterogeneous Social Networkmentioning
confidence: 99%